A tufted angioma - Prasuna, Aeerabolli (Indian Dermatol Online J, 2015)
Tufted angioma (TA) is a rare, benign, cutaneous angiomatous proliferation. It is more common in children, usually presenting as red-purple painful plaques on the trunk. We describe here a TA observed at nine months of age, appearing initially over the retroauricular area, gradually extending to involve skin of neck and trunk by two years of age. This case of a large TA (7 × 12 cm) in an Indian male child is reported here due to its rare presentation.